Inhabiting compassion: A pastoral theological paradigm - Zylla, Phil C. (HTS teologiese studies, 2017)
Inspired by the vision of care in Vincent van Gogh’s depiction of the parable of the Good Samaritan, this article offers a paradigm for inhabiting compassion. Compassion is understood in this article as a moral emotion that is also a pathocentric virtue. This definition creates a dynamic view of compassion as a desire to alleviate the suffering of others, the capacity to act on behalf of others and a commitment to sustain engagement with the suffering other. To weave this vision of compassion as a habitus rather than a theoretical construct, the article develops three phases of compassion: seeing, companioning and sighing. This framework deepens and augments a pastoral theological paradigm of compassion with the aim of inculcating an inhabited compassion in caregivers and the communities in which they participate.